KEDUDUKAN GURU SEBAGAI PENDIDIK - St. Aisyah Abbas (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2017)
Guru is one of the key elements in the education system, even the other components will not mean much if the teacher in the learning process is not able to interact with learners with good and perfect. Duties and functions of teachers in improving the quality of education is a process containing a course of conduct of teachers and learners on reciprocal relationships that take place in an educational situation for achieving educational goals, so that the process contained multi-function of the teacher. Duties and functions of the teacher in question is either associated with learners, teaching materials, and educational administration, and others. The position of teachers as educators greatly influence the success of an educational institution, as learners as educational input will be colored by the extent to which the teacher's role in developing the potential of learners. As a teacher as a learning resource, as a facilitator, as a manager of a class, as a learning demonstrator, as mentors, guides and evaluators. All of this must be used as the primary capital to be a professional teacher.